1993
DOI: 10.1103/physrevlett.70.3927
|View full text |Cite
|
Sign up to set email alerts
|

New high-pressure transformation in α-quartz

Abstract: Recent experimental and theoretical studies report that quenched pressure-amorphized a-quartz is elastically anisotropic and displays a reversal of anisotropy with respect to the original crystallographic orientation. We demonstrate that samples recovered from static compression experiments of a-quartz exhibit an unusual pressure-induced microstructure, which arises from a new phase transformation in aquartz at 21 GPa. Upon decompression, the high-pressure phase reverts to a quartzlike structure in a twinned s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
99
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 176 publications
(118 citation statements)
references
References 25 publications
18
99
1
Order By: Relevance
“…3 ␣-quartz, the stable form at ambient conditions, undergoes a crystalline-to-crystalline transition at 21 GPa prior to pressure-induced amorphization. [4][5][6][7] Similar transformations have been observed for cristobalite and for the isomorphic forms of quartz, GeO 2 and AlPO 4 . [8][9][10][11] These transitions are associated with the formation of tetrahedral networks, and at higher pressure, increases in cation coordination number.…”
Section: Introductionsupporting
confidence: 50%
See 2 more Smart Citations
“…3 ␣-quartz, the stable form at ambient conditions, undergoes a crystalline-to-crystalline transition at 21 GPa prior to pressure-induced amorphization. [4][5][6][7] Similar transformations have been observed for cristobalite and for the isomorphic forms of quartz, GeO 2 and AlPO 4 . [8][9][10][11] These transitions are associated with the formation of tetrahedral networks, and at higher pressure, increases in cation coordination number.…”
Section: Introductionsupporting
confidence: 50%
“…78 This transition pressure is close to that of the experimentally reported crystalline-crystalline phase transition documented in high-pressure hydrostatic experiments of quartz. 7 The present study strongly suggests that when quartz is compressed in a nonhydrostatic manner with the stress along c greater than that along a and b, this instability is postponed to higher pressures. The resulting strain allows the silicon atoms to experience a different oxygen environment than would normally be encountered under hydrostatic conditions.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…However, a single crystal X-ray diffraction study of quartz (in argon) showed no pressure-induced amorphization up to 19.3 GPa [31]. At 21 GPa, the quartz II phase and new lines are observed in a nonhydrostatic pressure medium [32,33]. The quartz II and the new phase with space group P2 1 =c appeared around 19-21 GPa in a quasihydrostatic pressure medium and both phases persisted stably up to 40 GPa [35].…”
Section: Examplesmentioning
confidence: 99%
“…The observed pressureinduced amorphization of scolecite and mesolite has been attributed to the increased spreading of the T±O±T angles caused by the progressive disruption of 4-member rings. This process has been observed in other materials [10,20,21] and could be the cause of pressure-induced amorphization of zeolite Li-A and Na-A. However, since the unit cell volume for scolecite is much smaller than that of Linde A and the pore and channels in the Linde A zeolites are much larger and more extensive, a comparison between the amorphization pressures is limited.…”
Section: Pressure-induced Amorphizationmentioning
confidence: 95%